Про закономірності у зміні температури чавуну на випуску з доменної печі - Кузнецов, М.С.; Крячко, Г.Ю.; Стороженко, С.А. (Physico-technological Institute of Metals and Alloys, 2023)
The regularities of changes in the temperature of cast iron at the outlet in the process of improving the technology of melting cast iron are considered. Depending on the ratio of time spent on the accumulation of melting products and their release from blast furnaces, it is proposed to classify the output into three main types: periodic with a not mobile coke nozzle, periodic with a movable coke nozzle and quasi-continuous, when the duration of the accumulation of melts is significantly less than the time of release. The results of the study of changes in the temperature of cast iron in the process of production on blast furnaces with a volume of 1500 and 1386 m3 are presented. The technology of furnace operation was recognized by the adopted slag mode and the furnace hearth before the output of melting products. In the research period, the productivity of blast furnaces varied between 50–55 t/m2·24 h, and the maximum output was 190 to 370 t. The temperature of the cast iron in the process of outlet was measured with high temperature pyrometer NT-6898. The metal distance to the eyepiece is of 2.0–2.5 m. The pyrometer test was carried out with a simultaneous measuring of temperature and the thermocouple plunging TPR 0290M. Declinations of the readings of thermocouples from the readings of a pyrometer were in the range of 0.2–1.2 %. In the process of research the characteristic minimum in a received cast iron temperature changes curve were found, in the period of 0.5–0.67 hours of the normalized release scale. It was determined that the received results are coincided with the results of previous researches, carried out on furnaces with a “floating” coke nozzle. According to the balance of forces, which act on the coke oven nozzle, the reasons of the determined regularities temperature charges in the cast iron release were explained. It is shown that measuring the temperature of cast iron at the rate of production of melting products gives not only information about changes in the heating of the hearth, but also can be used as an indicator of the processes occurring in the coke nozzle.